Oral Cancer Public Awareness: A Population-Based Study in Libya - ELallaky, Hend; Zinelabedin Mohamed; Alshareef Haweel; Ekram Adaiem; Emtenan Alzlitny; Ezuldeen Abdaleem; Zeiad Almsmary; Hadeel Suliman (AlQalam Journal of Medical and Applied Sciences, 2025)
This paper focuses on assessing the level of oral cancer awareness in Libya and the population's interest in learning about this disease, as well as determining the participants' ability to detect oral cancer at an early stage and seek help. In this cross-sectional study, 504 participants were selected from a random sample of Libyan citizens for the community overview. Both paper and Google Forms® adaptations of the overview were made based on prior inquiries about surveys. ‎We found that one-third of the population lacks awareness about oral cancer signs, while more than half of them underestimate the actual prevalence of the disease. In addition, about 72 % were not aware of how to check their mouths for signs of oral tumor, while the majority of them 93 % are seeking to learn about the way to self-check. The results show a high level of unawareness concerning the need for enhanced public education and outreach efforts. Spreading awareness could empower individuals to perform self-checks, contributing to earlier detection and better outcomes.